Home fire drills - Raatma, Lucia (Mankato, Minn. : Bridgestone Books, 1999)
Explains the importance of planning what to do in case of fire in your house and tells how practicing fire drills can help you to be safe.
Includes bibliographical references (p. 24) and index.
Keywords: Fire drills -- Juvenile literature; Dwellings -- Safety measures -- Juvenile literature; Fire drills; Dwellings -- Safety measures; Safety